Selective hydrogenation of nitriles to primary amines catalyzed by a novel iron complex. Issue 9 (15th December 2015) - Chakraborty, Subrata; Leitus, Gregory; Milstein, David
Abstract : A novel complex based on earth-abundant iron, and its application in the catalytic homogeneous hydrogenation of (hetero)aromatic, benzylic, and aliphatic nitriles to selectively form primary amines is discovered. Abstract : Hydrogenation of nitriles to primary amines constitutes an atom-efficient and environmentally benign synthetic reaction. Herein we present a novel complex based on earth-abundant iron, and its application in the catalytic homogeneous hydrogenation of (hetero)aromatic, benzylic, and aliphatic nitriles to selectively form primary amines.